Morphological diagnosis of the eggs of stored-products mites - Kucerova, Zuzana; Stejskal, Vaclav (Experimental & applied acarology, 2009)
Eggs of 13 species of common, economically important stored-product pest mites (Acarus siro, A. gracilis, Tyrophagus putrescentiae, T. brevicrinatus, Tyroborus lini, Aleuroglyphus ovatus, Caloglyphus redikorzevi, C. oudemansi, Lepidoglyphus destructor, Glycyphagus domesticus, Aeroglyphus robustus, Chortoglyphus arcuatus and Carpoglyphus lactis) from four families (Acaridae, Glycyphagidae, Chortoglyphidae, Carpoglyphidae) were studied in order to build a diagnostic key. The morphological study dealt with shape, size and surface sculpturing of eggs. Morphological details were visualised using scanning electron microscopy. A key for distinguishing eggs at genus and species level was developed for the major stored-product mites.
Keywords: Acaridae; kontrola škůdců; Pest Control; ovum; zvířata; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Surface Properties; povrchové vlastnosti; Animals; Ovum